Softness, Elasticity, and Toughness of Polymer Networks with Slide-Ring Cross-Links - Mayumi, Koichi; Liu, Chang; Yasuda, Yusuke; Ito, Kohzo (Gels, 2021)
Slide-ring (SR) gels cross-linked by ring molecules are characterized by softness (low Young’s modulus), elasticity (low hysteresis loss), and toughness (large fracture energy). In this article, the mechanical and fracture properties of SR gels are reviewed to clarify the physical understanding of the relationship between the molecular-level sliding dynamics of the slide-ring cross-links and macroscopic properties of SR gels. The low Young’s modulus and large fracture energy of SR gels are expressed by simple equations as a function of the degree of sliding movement. The dynamic fracture behaviors of SR gels gives us the time scale of the sliding dynamics of the cross-links, which is at the micro-sec scale. The fast sliding motion of the cross-links leads to the elasticity of the SR gels. The SR concept can be applied to solvent-free elastomers and composite materials.